Establishment Network by Using FSO Link Based on MD Code for Hybrid SCM-SAC-OCDMA Wireless System - Rashid Ali Fayadh; Mousa K. Wali; Mehdi F. Bonneya (Institute of Advanced Engineering and Science, 2018)
Since the wireless systems are working under nature environments and influenced by turbulence, weather in Iraq that leads to extended amount of fading signal, dissipation or attenuation. Basic “hybrid Subcarrier Multiplying Spectral Amplitude Coding (SCM-SAC) of Optical Code Division Multiple Access (OCDMA)